Global Security Initiative and the Development of Contemporary International Law - Xu, Kun; Lv, Zhiping; Li, Jiayi (Transactions on Social Science, Education and Humanities Research, 2024)
President Xi put forward the Global Security Initiative for the first time in his speech at the opening ceremony of the Boao Forum for Asia Annual Conference in 2022. Echoing the Global Development Initiative, the Global Security Initiative coordinates the maintenance of traditional and non-traditional security, which is committed to building a new system of global security governance characterized by the nature of “soft law” in international law. Meanwhile, the Global Security Initiative has had a vital impact on the value behavior orientation and the development of basic principles of contemporary international law. In addition, international law plays a role in guaranteeing the Global Security Initiative, which is reflected in its help to resolve various risks in security governance, prevent and tackle disputes in global security governance, provide institutional guarantees to maintain national interests in the promotion of Global Security Initiative and improve international harmony.